2009
DOI: 10.1182/blood.v114.22.2015.2015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Pulmonary Arterial Hypertension in Hemoglobin E/ β-Thalassemia Patients.

Abstract: 2015 Poster Board I-1037 Introduction: Pulmonary arterial hypertension (PAH) associated with thalassemia (Thal) hemoglobinopathy is now an accepted clinical entity. Most of the reports are in sickle cell disease and splenectomized β-Thal patients. Once manifested, it connotes poor prognosis. We herein present its prevalence and predictors in hemoglobin E/β-Thal (E/β-Thal) patients. Patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…Splenectomy, advanced age and severe anemia remained the important risk factors for pulmonary hypertension risk similar to previous reports . Although splenectomy was the strong factor for pulmonary hypertension risk in patients with β‐thalassemia in this cohort, there were, however, no associations between splenectomy and pulmonary hypertension risk in patients with α‐thalassemia and combined α and β‐thalassemia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Splenectomy, advanced age and severe anemia remained the important risk factors for pulmonary hypertension risk similar to previous reports . Although splenectomy was the strong factor for pulmonary hypertension risk in patients with β‐thalassemia in this cohort, there were, however, no associations between splenectomy and pulmonary hypertension risk in patients with α‐thalassemia and combined α and β‐thalassemia.…”
Section: Discussionsupporting
confidence: 88%
“…This finding might be due to the fact that patients with β‐thalassemia had the more severe phenotype than patients with α‐thalassemia and combined α and β thalassemia. The prevalence of pulmonary hypertension risk in patients with thalassemia in this cohort is lower than previous studies in Thailand (10.9% vs 37.5% and 29%) . The low prevalence of pulmonary hypertension risk in this study might be explained by three main factors including (i) the differences in the diagnostic criteria for pulmonary hypertension risk by echocardiography, because in this study pulmonary hypertension risk was defined by peak tricuspid regurgitation velocity > 2.9 m/s, which is a more strict criterium than in previous studies, however, this higher cut‐off will miss some cases of pulmonary hypertension risk; (ii) The high numbers of patients with α‐thalassemia in this study's cohort demonstrated that pulmonary hypertension risk is less common in these patients; and (iii) Pulmonary hypertension risk was frequently found in the third decade of life , but the majority of patients in this study were younger than 30 yr old (141, 64.4%).…”
Section: Discussioncontrasting
confidence: 68%
“…Advancing age and a history of splenectomy are major risk factors for PH in this population 24–26,28,29 . In one study of patients with TM, the degree of anemia, number of transfusions, and serum ferriten levels did not appear to correlate with risk, 10 while a more recent report found ferriten to be a strong indicator of an elevated TRV in patients with both TM and TI 30 .…”
Section: Prevalence and Risk Factorsmentioning
confidence: 95%
“…A remarkably similar prevalence was also reported in patients with hemoglobin E/β‐thalassemia in Thailand. An abnormally high TRV was identified in 37% of 110 Thai patients screened for PH, and was associated with splenectomy, a high hemolytic rate, an increase in activated platelets and nucleated red blood cells, and chronic inflammation and elevated circulating adhesion molecules 26 . Although limited data have been reported in children, a recent study out of Cairo found a 37.5% prevalence of PH in children with TM 27 .…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…6 Advanced age and a history of splenectomy are major risk factors for PH in this population. [20][21][22][23][24][25] Since strict compliance with chronic transfusion and chelation therapy to prevent iron overload cuts the condition of heart failure, and prevents PH, [26][27][28] thalassemia patients may be at higher risk for the development of PH.…”
mentioning
confidence: 99%